1911 N.Y. Laws 443 - (:unkn) unknown (My University, 1911)
Ch. 195: The "Sullivan Law." Expanded criminal possession of all handguns, concealed or otherwise, without a government-issued license. Later amended in 1913 such that Magistrates could issue only if applicants proved "good moral character" and "proper cause." 1913 N. Y. Laws ch. 608, §1, p. 1629.
Keywords: CARRY; CARRY - CONCEALED